How does Environmental Geochemistry Affect Elephant Movement? - Sach, Fiona (2020)
The aim of this study was to better understand how environmental geochemistry influences mineral provision to African savanna elephants, and thus their home range size and movement choices. Due to increasing human activity and competition for land-use, African savanna elephants globally are constrained into smaller areas. This presents elephants with nutritional challenges, requiring adaptation to their movement patterns to obtain sufficient mineral intake. An in situ experiment was enabled by the Palabora Mining Company (PMC) property, and the surrounding national park lands in South Africa, providing a case study of contrasting environments. The PMC mines copper, phosphates and other minerals and the locale is proposed to act as a micronutrient hotspot for elephants, due to its unique local geochemistry. The increased presence of elephants at the PMC, and incursion to the mine with associated disruption of mining activities has resulted in human-elephant conflict. It was hypothesised that elephants reside within the locality of the PMC property, owing to its potential as a micronutrient hotspot. To determine the influence of geochemistry on elephant movement, optimum bioindicators of mineral nutritional or potentially toxic element (PTE) status were required, prior to studying the PMC associated elephant populations, to differentiate between patterns of movement between national park lands and surrounding reserves (background) and mineral processed lands at the PMC (elevated). The validation of optimum bioindicators (e.g. toenail, tail hair, plasma or faeces) for mineral or PTE status was achieved by collection and elemental analyses of environmental and biological samples from 21 elephants at five UK zoos. A linear mixed model showed that toenail was the best bioindicator of intake for Mg, P, K, Se and As, with keeper-fed diet being the strongest predictor (P < 0.05 for all). Tail hair reflected As and Fe intake (P<0.001, 0.029), and Ca intake was reflected in faecal samples (P= 0.019). Validated methods of sampling and analysis were applied to the micronutrient hotspot around the PMC, with sampling and analysis of environmental (soil, water, plants) and biological (faecal and tail hair) samples from elephant populations at the mine and in the surrounding national park and reserves. Results showed that the geochemistry differs at the PMC compared to the surrounding areas, with significant elevations shown in all 15 investigated elements in soil. Significant elevations were seen in Mg, P, Cu, As, Cd, Pb and U in faecal samples at the mine compared to the non-mine samples (P>0.05). Tail hair samples from elephants collared at the PMC were significantly higher in Cd and significantly lower in K and Se compared to non-mine counterparts. Correspondingly, the home range of animals collared at the PMC was 59% smaller (P= 0.001) than conspecifics from adjacent locations. This multi-disciplinary study demonstrated the importance of environmental geochemistry on mineral provision, and subsequent influence on elephant population movement, using this case study of contrasting environments and the micronutrient hotspot at the PMC. Application of this information will be valuable to conservation managers, to influence elephant movement and thus reduce associated human-elephant conflicts. Equally, this work benefits zoo elephants, providing comparative baseline data to enable assessment of mineral status in captivity, and in turn this project demonstrates how zoo based research can inform the management of wild counterparts.